THE POWER OF 'THREE CREATION': TRANSFORMING TOURISM MANAGEMENT EDUCATION WITH IDEOLOGY AND INNOVATION - Han, Chen Yu; Lin, Zhang Wei (Research Journal of Education and Allied Studies, 2024)
In the era of new liberal arts, higher education institutions face the vital task of nurturing students' innovation, entrepreneurial mindset, and creativity. This imperative extends to applied disciplines like tourism management, where educational reform is increasingly pressing. The goals of tourism management programs have evolved in response to the dynamic socioeconomic landscape and the evolving expectations of tourists. Nurturing comprehensive innovation, entrepreneurship, and creativity among tourism management students is paramount, and it demands the integration of "three creations" education with professional ideology within the new liberal arts framework. This paper explores the implementation and evolution of "three creations" education in tourism management through innovative classroom methods, extensive literature analysis, and comprehensive questionnaire surveys. The study advocates a synergistic approach that combines "three creations" education with professional ideology and politics to guide the cultivation of students. The ultimate objective is to offer valuable insights for education and teaching reforms in tourism management programs, ensuring that students develop a sound life perspective and values while honing their professional skills. The proposed synergistic nurturing model aims to contribute to the field of tourism management by fostering holistic education and addressing theoretical and practical challenges in cultural education.